Education and Training on the Production of Organic Fertilizers and Biopesticides for Cocoa Farmers in Pulukan Village, Jembrana, to boost organic cocoa production: Education and Training on Making Organic Fertilizers and Biopesticides for Cocoa Farmers - I Nyoman Rai; I Made Sudana; Setiyo Yohanes; I Wayan Wiraatmaja (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
Pulukan Village, located in the Jembrana Regency of Bali, is one of the primary communities that produce organic cocoa. The huge demand for organic cocoa beans has not been satisfied due to the poor production per hectare. One of the causes is that cocoa farmers in the village have trouble obtaining the recommended volumes of organic fertilizers and biopesticides. To raise the yield of organic cocoa, this service is provided to farmers to enhance their knowledge and ability to create organic fertilizers and biopesticides from local components. The activities are implemented through counselling and training on producing organic fertilizers and biopesticides, followed by support in applying organic fertilizers and biopesticides. Participants in training and mentoring are encouraged to work together and learn concurrently. The implementation of the counselling on the production of organic fertilizers and biopesticides was excellent, as indicated by the fact that 93.33 per cent of participants said they comprehended the material presented very well, and 100 percent said it was fascinating and very beneficial. Participants could produce excellent organic fertilizers and biopesticides due to training activities involving direct practice. As a result of training in plots, organic fertilizers, and biopesticides can improve farmers' ability to directly implement fertilizing methods and disease pest management in organic cocoa farming. Applying organic fertilizers and biopesticides in the plot revealed that cocoa trees treated with organic fertilizers and biopesticides had greater growth and fewer disease-causing insect infestations than control trees.This motivated the service volunteers to implement the plot's best practices on their organic cocoa crops.